The human and social dimensions of invasion science and management. (1st January 2019) - Shackleton, Ross T.; Larson, Brendon M.H.; Novoa, Ana; Richardson, David M.; Kull, Christian A.
Abstract: Biological invasions are a leading cause of global environmental change given their effects on both humans and biodiversity. Humans introduce invasive alien species and may facilitate their establishment and spread, which can alter ecosystem services, livelihoods, and human well-being. People perceive the benefits and costs of these species through the lens of diverse value systems; these perspectives influence decisions about when and where to manage them. Despite the entanglement of humans with invasive alien species, most research on the topic has focused on their ecological aspects. Only relatively recently have the human and social dimensions of invasions started to receive sustained attention in light of their importance for understanding and governing biological invasions. This editorial draws on contributions to a special issue on the " Human and Social Dimensions of Invasion Science" and other literature to elucidate major trends and current contributions in this research area. We examine the relation between humans and biological invasions in terms of four crosscutting themes: (1) how people cause biological invasions; (2) how people conceptualise and perceive them; (3) how people are affected – both positively and negatively – by them; and (4) how people respond to them. We also highlight several ways in which research on the human and social dimensions of invasion science improves understanding, stakeholder engagement, and management. Highlights: Biological invasions inherently encompass social and ecological aspects. More research on the human and social dimensions of invasive alien species is needed. People cause, conceptualise and perceive, are affected by, and respond to invasions. Improved understanding of this will aid the management of invasives.